2002
DOI: 10.1159/000064424
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Control of Growth Hormone Secretion by Somatostatin in Rat Pituitary GC Cells: sst<sub>2</sub> but Not sst<sub>1</sub> Receptors Are Coupled to Inhibition of Single-Cell Intracellular Free Calcium Concentrations

Abstract: Rat pituitary tumor cells (GC cells) exhibit spontaneous oscillations of intracellular free calcium concentration ([Ca2+]i) that allow continuous release of growth hormone (GH). Of the somatostatin (SRIH) receptor subtypes (sst receptors) mediating SRIH action, sst1 and sst2 receptors are highly expressed by GC cell membranes. In the present study, the effects of sst1 or sst2 receptor activation on single-cell [Ca2+]i were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 39 publications
(82 reference statements)
2
24
0
Order By: Relevance
“…In somatotropinomas, sst 2 is the main receptor inhibiting voltage-gated Ca 2+ current (Yang et al 2007) and it has also been suggested to decrease GH release through the inhibition of the voltage-dependent Ca 2+ channels (Florio et al 2003). These evidences are confirmed by previous studies performed in rat anterior pituitary GC cells, an adenoma cell line which exhibits pacemaker activity and concomitant spontaneous oscillations of [Ca 2+ ] i and GH secretion (Cervia et al 2002b). In GC cells, sst 2 activation is responsible for the [Ca 2+ ] i decrease and the block of Ca 2+ transients which, in turn, results in the sst 2 -mediated decrease of GH secretion (Petrucci et al 2000;Cervia et al 2002aCervia et al ,b, 2003.…”
Section: Introductionsupporting
confidence: 72%
See 3 more Smart Citations
“…In somatotropinomas, sst 2 is the main receptor inhibiting voltage-gated Ca 2+ current (Yang et al 2007) and it has also been suggested to decrease GH release through the inhibition of the voltage-dependent Ca 2+ channels (Florio et al 2003). These evidences are confirmed by previous studies performed in rat anterior pituitary GC cells, an adenoma cell line which exhibits pacemaker activity and concomitant spontaneous oscillations of [Ca 2+ ] i and GH secretion (Cervia et al 2002b). In GC cells, sst 2 activation is responsible for the [Ca 2+ ] i decrease and the block of Ca 2+ transients which, in turn, results in the sst 2 -mediated decrease of GH secretion (Petrucci et al 2000;Cervia et al 2002aCervia et al ,b, 2003.…”
Section: Introductionsupporting
confidence: 72%
“…CaMKII activation and GH secretion are reported to be correlated also in rat GH 3 tumor pituitary cells (Kanasaki et al 2002). Homologous normal and tumoral pituitary cells, including GC cells, display the same type of secretory mechanisms in vitro (Cervia et al 2002b;Stojilkovic et al 2005). Thus, CAMKIIβ activity may be required for GH production also in normal somatotropes of mammals, as demonstrated in fishes .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Calcium and activated G proteins are known to regulate the exocytosis of different factors, i.e., chemokines, synergistically from the activated macrophages, although a Ca 2ϩ -independent component may also be involved [76]. SRIF receptor coupling to Ca 2ϩ homeostasis is well established [2] as well as the fact that SRIF receptors may regulate exocytosis through mechanisms dependent and independent on Ca 2ϩ [2,35,51]. Whether the SRIF system couples to Ca 2ϩ homeostasis in human macrophages remains to be established.…”
Section: In Human Macrophagesmentioning
confidence: 99%